Development and shelf-life of ready-to-serve frozen fish curry from Indian mackerel (Rastrelliger kanagurta) - Rao, V Suryaprakash; Sudhakara, N S; Reddy, K Punna (Indian Journal of Fisheries, 2011)
Indian mackerel (Rastrelliger kanagurta) which forms a substantial proportion of the marine fish landingsin India was utilized for the development of a ready-to-serve frozen fish curry. The products stored at-20Â°Cfor 6 months were analysed for the quality characteristics. A good correlation was observed between thesensory assessment and chemical parameters. Skinless and boneless flakes in curry were preferred overskinon and boneon steaks in curry.